It’s Public Knowledge: The National Digital Archive of Datasets - Sleeman, Patricia (Archivaria, 2004)
This article describes the history and development of the National Digital Archive of Datasets, a service run by the University of London Computer Centre for the National Archives of England. It discusses the project in light of the context in which it emerged in the 1990s, its departure in approach from traditional data archives, and the range of archival functions. Finally, it offers reflections on the project as whole. RÉSUMÉ Cet article décrit l’histoire et le développement du National Digital Archive of Datasets, un service offert par le centre informatique de l’Université de Londres pour les Archives nationales de l’Angleterre. L’auteure présente le contexte dans lequel le projet a émergé dans les années 1990, son approche qui diffère de celle des archives de données informatiques traditionnelles, ainsi que la gamme de ses fonctions archivistiques. Finalement, elle offre des réflexions sur le projet dans son ensemble.